2000
DOI: 10.1029/2000jd900361
|View full text |Cite
|
Sign up to set email alerts
|

Photochemical production of gas phase NOx from ice crystal NO3

Abstract: Abstract. Recent measurements have demonstrated that sunlight irradiation of snow results in the release of significant amounts of gas phase NO• (NO + NO2). We report here the results of a series of experiments designed to test the hypothesis that the observed NOz production is the result of nitrate photolysis. Snow produced from deionized water with and without the addition of nitrate was exposed to natural sunlight in an outdoor flow chamber. While NOx release from snow produced without added NO• was minimal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
157
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 164 publications
(165 citation statements)
references
References 44 publications
(2 reference statements)
8
157
0
Order By: Relevance
“…4a). Experiments at Summit by Honrath et al (1999Honrath et al ( , 2000a showed upward fluxes of NO x (2.52 × 10 8 molecules cm −2 s −1 ) from the photolysis of nitrate in snowpack during the summertime, leading to an enhancement of NO x levels in the surface layer by approximately 20 pptv, which was comparable to surface NO x mixing ratios in the Arctic from other sources. Similar results were found over the East Antarctic Plateau snow and ice sheet (Frey et al, 2013;Legrand et al, 2014).…”
Section: No Xmentioning
confidence: 65%
“…4a). Experiments at Summit by Honrath et al (1999Honrath et al ( , 2000a showed upward fluxes of NO x (2.52 × 10 8 molecules cm −2 s −1 ) from the photolysis of nitrate in snowpack during the summertime, leading to an enhancement of NO x levels in the surface layer by approximately 20 pptv, which was comparable to surface NO x mixing ratios in the Arctic from other sources. Similar results were found over the East Antarctic Plateau snow and ice sheet (Frey et al, 2013;Legrand et al, 2014).…”
Section: No Xmentioning
confidence: 65%
“…For example, liquid-phase kinetics and mechanisms can explain the direct photolysis of nitrate, nitrite, and hydrogen peroxide on/in ice made from slowly frozen solutions, conditions where we expect solutes to be in LLRs. [19][20][21][22][23] However, in many cases liquid-phase chemistry cannot be extrapolated to ice…”
Section: Introductionmentioning
confidence: 99%
“…These processes result in the formation of gases, including oxidized nitrogen, halogen species, organic compounds and hydrogen peroxide, which subsequently are released into the atmosphere and perturb the gas-phase HO x budget and cycling (e.g. Dibb et al, 1998Honrath et al, 1999Honrath et al, , 2000aSumner and Shepson, 1999;Zhou et al, 2001;Swanson et al, 2002Swanson et al, , 2003.…”
Section: Ozone Uptake To Snowmentioning
confidence: 99%
“…Recent research in Greenland, Antarctica and at a midlatitude site in Michigan has shown that photochemical processes in the sunlit snowpack can also lead to production of substantial amounts of nitrogen oxides (NO x =NO+NO 2 ) by photodenitrification (Honrath et al, 1999(Honrath et al, , 2000aJones et al, 2000;Cotter et al, 2003). In a study at Summit, Greenland, Peterson and Honrath (2001) measured diurnal cycles of UV radiation, NO x and ozone in interstitial air (the air between snow grains in the snowpack; also referred to as firn air) at 30 cm depth and compared those measurements with data from above the surface.…”
Section: Ozone Uptake To Snowmentioning
confidence: 99%